2019
DOI: 10.1093/bioinformatics/btz837
|View full text |Cite
|
Sign up to set email alerts
|

Differential privacy under dependent tuples—the case of genomic privacy

Abstract: Motivation The rapid progress in genome sequencing has led to high availability of genomic data. However, due to growing privacy concerns about the participant’s sensitive information, accessing results and data of genomic studies is restricted to only trusted individuals. On the other hand, paving the way to biomedical discoveries requires granting open access to genomic databases. Privacy-preserving mechanisms can be a solution for granting wider access to such data while protecting their o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 25 publications
2
42
2
1
Order By: Relevance
“…Later, for location datasets, Liu et al (2016) showed how an adversary with the knowledge of pairwise dependencies between tuples can predict users’ locations ( Liu et al , 2016 ). Recently, Almadhoun et al (2020) analyzed the decrease in the privacy guarantees of DP-based mechanisms when there are dependent tuples in a statistical genomic dataset.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…Later, for location datasets, Liu et al (2016) showed how an adversary with the knowledge of pairwise dependencies between tuples can predict users’ locations ( Liu et al , 2016 ). Recently, Almadhoun et al (2020) analyzed the decrease in the privacy guarantees of DP-based mechanisms when there are dependent tuples in a statistical genomic dataset.…”
Section: Related Workmentioning
confidence: 99%
“…In this work, we demonstrate the scale of attribute inference attacks using differentially private results of two complex and real-life queries over statistical genomic datasets [compared to the simple sum query considered in the study by Almadhoun et al (2020) ]. As opposed to Liu et al (2016) , which only considers pairwise correlation between the tuples, we consider interdependent correlations between dataset participants.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations